Upaya Meningkatan Mutu Pendidikan di Indonesia - Amiruddin Siahaan; Rizki Akmalia; Aina Ul Mardiyah Ray; Ari Wibowo Sembiring; Era Yunita (Journal on Education, 2023)
The purpose of this research was conducted to examine how efforts to improve education quality management at SMP PAB 10 Medan Estate. Efforts to improve to achieve quality education do not only fulfill the input and output aspects, but what is more important are the process aspects, what is meant is decision making, program management, institutional management processes, teaching and learning processes and monitoring and evaluation processes, provided that the process teaching and learning has the highest level of importance compared to other processes. One of the educational problems faced by the Indonesian nation today is the low quality of education at every level and educational unit, especially higher education. Various efforts have been made to improve the quality of national education, including through various trainings and improving the competence of lecturers, procuring books and media, improving educational facilities and infrastructure, and improving the quality of campus management. However, various indicators of the quality of education have not shown significant improvement. Some tertiary institutions, especially in big cities, have shown encouraging improvements in the quality of education, but most are still apprehensive. The quality of education are two terms that come from quality and education, meaning that they refer to the quality of products produced by educational institutions or schools. That is, it can be identified from the number of students who have achievements, both academic and other achievements, as well as graduates relevant to the goals.